Endolymphatic sac surgery: past and present controversies - Gibson, W. P. R. (Frontiers in Neurology, 2025)
The history of endolymphatic sac surgery is presented. The original concept of passive drainage is challenged as the physiology of the endolymphatic sac is gradually elucidated. Surgery causes damage to the delicate cells with the concept of endolymphatic sac excision and endolymphatic duct clipping discussed. The author presents a hypothesis of how vertigo attacks occur.